The Potential Value of Targeting Ferroptosis in Early Brain Injury After Acute CNS Disease - Chen, Junhui; Wang, Yuhai; Wu, Jiyun; Yang, Jiaji; Li, Mingchang; Chen, Qianxue (Frontiers in Molecular Neuroscience, 2020)
Spontaneous subarachnoid hemorrhage (SAH) is a common cerebrovascular disease with high mortality. There is much basic research had confirmed that the molecular mechanism of early brain injury (EBI) after SAH. Neuron's death and dysfunction are important reasons for the neurological dysfunction in patients with SAH. Ferroptosis is a nonapoptotic form of cell death, the classical characterize base on the iron-dependent accumulation of toxic lipid reactive oxygen species. Previously studies had indicated that this mechanism in regulated cell death events observed in many diseases included cancer, tumor resistance, Alzheimer’s disease, Parkinson's disease, stroke, and intracerebral hemorrhage, etc. And it also may play a very important role in early brain injury after SAH. Outstanding issues include the relationship between ferroptosis and other forms of cell death after SAH, the specific molecular mechanisms of EBI, how to activate or inhibit ferroptosis can be exploited to achieve desirable anti-EBI, and need to find a new molecular markers of ferroptosis that can be used to detect and study this process in vivo after SAH.